Congenital Anatomical Variant with Cranial Origin of Internal Iliac Arteries - Rossi, Umberto G.; Ierardi, Anna M.; Cariati, Maurizio (AORTA, 2021)
We report the case of a 73-year-old male who underwent abdominal multidetector computed tomography with vascular reconstruction that highlighted a congenital variant of iliac arteries. Iliac artery anatomical variants are exceedingly rare and only a few cases have been reported in the literature.
Keywords: iliac artery; vascular; variant; congenital; anatomy; imaging